2014
DOI: 10.5935/abc.20140196
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Syndrome in Patients Admitted with Acute Coronary Syndrome

Abstract: BackgroundBurnout Syndrome is the extreme emotional response to chronic occupational stress, manifesting as physical and mental exhaustion. Although associated with higher prevalence of cardiovascular risk factors, no study so far has evaluated whether the Burnout Syndrome could be a prevalent factor in non-elderly individuals active in the labor market, admitted for acute coronary syndrome (ACS).ObjectiveTo evaluate the prevalence of the Burnout Syndrome in non-elderly, economically active patients, hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…23 A recent study reported a 4.1% prevalence of burnout syndrome and approximately 80%–90% stress among acute coronary syndrome patients. 24 However, the prevalence in HF patients has not been reported till date, yet it is plausible that a similar rate will be observed. Therefore, we prospectively investigated the impact of metoprolol (a moderately lipophilic β blocker) treatment on change in the mental status (depression, anxiety, and burnout syndrome) of CHF patients.…”
Section: Introductionmentioning
confidence: 98%
“…23 A recent study reported a 4.1% prevalence of burnout syndrome and approximately 80%–90% stress among acute coronary syndrome patients. 24 However, the prevalence in HF patients has not been reported till date, yet it is plausible that a similar rate will be observed. Therefore, we prospectively investigated the impact of metoprolol (a moderately lipophilic β blocker) treatment on change in the mental status (depression, anxiety, and burnout syndrome) of CHF patients.…”
Section: Introductionmentioning
confidence: 98%
“…The better-known risk factors for ACS are dyslipidemia, diabetes mellitus [1] , hypertension [2] and coronary vasospasm. Among less appreciated risk factors, hypercoagulable states such as hyperhomocycteinemia and antiphospholipid syndrome and extreme emotional response to chronic occupational stress (Burnout Syndrome) [3] are noted. Coronary vasculitis is the least appreciated cause of ACS that is subject to neglect among clinicians [4] .…”
Section: Perspectivementioning
confidence: 99%